2018
DOI: 10.18325/jkmr.2018.28.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Research of Eastern-Western Integrative Medicine Studies in Korea

Abstract: Objectives The purpose of this study is to analyze research trends on Eastern-Western integrative medicine in Korea. Methods We searched the studies on Eastern-Western integrative medicine in 5 Korean web database (NDSL, KoreanTK, KISS, OASIS, DBPIA). 66 research papers we founded. Results 13 papers were published at 2010. The studies on Eastern-Western integrative medicine were mainly published in the Journal of Society of Preventive Korean Medicine. 24 papers were case report, include 7 studies on neurology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In several earlier studies regarding CT, we found that the sample sizes were small and the type of KM used in CT was designated. In addition, the assessment of the effectiveness of CT mostly focused on “cooperation in the treatment”; there are few reports on the “cooperation in the diagnosis and examination.” [ 17 , 35 ] Our study design overcomes these limitations with a relatively large sample size, no restriction on the type of KM, and by including cooperation at all clinical steps, such as examination, diagnosis, and treatment to reflect a real-world scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In several earlier studies regarding CT, we found that the sample sizes were small and the type of KM used in CT was designated. In addition, the assessment of the effectiveness of CT mostly focused on “cooperation in the treatment”; there are few reports on the “cooperation in the diagnosis and examination.” [ 17 , 35 ] Our study design overcomes these limitations with a relatively large sample size, no restriction on the type of KM, and by including cooperation at all clinical steps, such as examination, diagnosis, and treatment to reflect a real-world scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on KWCT have been conducted steadily since the 1990s, and the most frequently published article type in this regard were case reports. 10 In addition, various studies have been conducted about the effectiveness of KWCT, 11 , 12 , 13 surveys on perception and satisfaction on the KWCT, 14 , 15 , 16 survey about the actual condition and status of the KWCT, 17 development of the KWCT system, 18 KWCT manual development, 19 and economic evaluation of KWCT. 20 Based on these studies, literature reviews have also been published such as regarding the effect of KWCT on musculoskeletal diseases, 21 combination drug treatment in KWCT, 22 and a research trend analysis on KWCT.…”
Section: Introductionmentioning
confidence: 99%
“…20 Based on these studies, literature reviews have also been published such as regarding the effect of KWCT on musculoskeletal diseases, 21 combination drug treatment in KWCT, 22 and a research trend analysis on KWCT. 10 However, in 2009, when cross-employment of other types of licensed medical doctors were allowed at the same hospital (Article 43 of the Medical Law), the KWCT system in Korea came to a fundamental turning point. Although some suggestions were made based on a literature review published before 2009 23 about activation strategies to overcome barriers of KWCT, it is not suitable at the present time when the KWCT system has changed fundamentally through cross-employment of medical doctors with different licenses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quantity and quality of studies using combined Korean medicine/CAM and Western medicine treatment leaves much to be desired. Han et al [4] reported that 60% of the 89 Korean clinical research papers that were published on combined medical treatment between 2011 and 2017, were case reports or non-randomized controlled studies (nRCTs). In 93 clinical studies on combined medical treatment, the interventions were limited by inadequate communication between clinical practice physicians administering oral medications and Korean medicine doctors.…”
Section: Introductionmentioning
confidence: 99%